Durdur Sdn. Bhd. - Yew, Li Qing; Heah, Hui Yin; Koh, Joey Ming Sui; Chow, Zisin (2025)
The name "DurDur Sdn. Bhd." is a creative combination of "durian" and a stylized repetition to create a brand that is memorable, playful, yet strong and easy to pronounce. It reflects the company's core identity that transforming durian husk waste into stylish and eco-friendly fashion products. The unique name emphasizes both the local cultural relevance of durian and the company’s innovative approach to sustainable materials. The DurDur logo is a modern and minimalist representation of the brand’s ecoconscious yet fashion-forward vision. It features a stylized, monogram-inspired “D” and reverse “D” forming a bold symbol that reflects the company’s initials. This clean, geometric approach makes the logo easily adaptable for fashion tags, accessories, and packaging. The black and white colour scheme presents a sleek and timeless aesthetic, aligning with the luxury feel of the brand while ensuring high contrast and visibility across different backgrounds. The strong letter mark conveys fashion, creativity, and modern elegance, making it suitable for both digital branding and product labelling. Overall, the logo’s bold and symmetrical structure represents balance between innovation and sustainability perfectly encapsulating DurDur’s mission to create stylish, ethical fashion from agricultural waste. It reflects the brand’s ambition to lead a new era of eco-friendly bag manufacturing in Malaysia and beyond.